Bio-synthesized tin oxide nanoparticles (SnO2 NPs) as a photocatalyst model - Buniyamin, Irmaizatussyehdany; Eswar, Kevin Alvin; Asli, Noor Asnida; Abd Halim, Muhamad Faizal; Khusaimi, Zuraida; Mahmood, Mohamad Rusop (Academica Press Solutions, 2023)
In the textile industries, most of the consumers attracted to colored fabrics. Unfortunately, the substance that use to color fabrics contributes serious environmental pollution. In this work, we have designed an environmental-friendly to control the negative effect using solution-based approach. By using this method, the cost can be reduced up to one-fourth from the commercial price. The non-toxic materials of tin (iv) oxide nanoparticles (SnO2NPs) were synthesized via green bio-synthesis. Bio-synthesis was conducted using the bioactive compound in Aquilaria Malaccensis (agarwood) leaves extracts. The photocatalytic activity of methylene blue (MB) degradation was investigated. The photocatalytic degradation was found to 82 % and 80 % with the presence of UV light, and fluorescent light, respectively. Both of the measurement has been done within 70 minutes. The result shows that SnO2 NPs could be the best option for efficiently, economically, and ecologically treating dye-polluted water.